Entrapment of "PV‐Tracker" guidewire in the pulmonary veins during atrial fibrillation ablation with PVAC Gold. Issue 11 (6th August 2018) - Fontenla, Adolfo; López‐Gil, María; Montilla, Isabel; Arribas, Fernando
Abstract: We report the entrapment of Pulmonary Vein Ablation Catheter (Medtronic, Minneapolis, MN, USA) and its guidewire within the right pulmonary veins in two patients. The catheters could be retrieved without complications but they were disabled in both cases. This nondescribed incident should be recognized by PVAC users since it may be a source of potential severe complications during pulmonary vein isolation procedures.